Why precision medicine is not the best route to a healthier world - Juan Pablo Rey-López; Thiago Herick de Sá; Leandro Fórnias Machado de Rezende (Universidade de São Paulo, 2018)
ABSTRACT Precision medicine has been announced as a new health revolution. The term precision implies more accuracy in healthcare and prevention of diseases, which could yield substantial cost savings. However, scientific debate about precision medicine is needed to avoid wasting economic resources and hype. In this commentary, we express the reasons why precision medicine cannot be a health revolution for population health. Advocates of precision medicine neglect the limitations of individual-centred, high-risk strategies (reduced population health impact) and the current crisis of evidence-based medicine. Overrated "precision medicine" promises may be serving vested interests, by dictating priorities in the research agenda and justifying the exorbitant healthcare expenditure in our finance-based medicine. If societies aspire to address strong risk factors for non-communicable diseases (such as air pollution, smoking, poor diets, or physical inactivity), they need less medicine and more investment in population prevention strategies.